Efektivitas model problem based learning dengan langkah polya terhadap keterampilan berpikir kritis pada penyelesaian soal cerita matematika kelas IV sekolah dasar - Mayra Robby Mauliona; Riyadi Riyadi (Didaktika Dwija Indria, 2025)
This research aims to determine the effectiveness of the Problem Based Learning model incorporating Polya's Steps in enhancing the critical thinking skills of fourth grade students in Cluster 1 Kyai Mojo, Pasar Kliwon District, Surakarta City. Quantitative approach was employed, utilizing a quasi-experimental design with a pretest-posttest control group. The study applied a probability sampling technique with a cluster random sampling method. Data collection uses a critical thinking skills test. Validity testing uses content validity, namely expert judgment and construct validity by testing research instruments. Data analysis included the Shapiro-Wilk normality test, Levene's homogeneity test, and hypothesis testing using the independent sample t-test. The findings revealed that the significance value of the hypothesis test was less than 0.001, indicating a value lower than the 0.05 (5%) significance threshold. A notable difference was observed in the average critical thinking skills between the control and experimental groups, with the control group scoring an average of 70.76, while the experimental group achieved an average of 80.48. These results demonstrate that the PBL model with Polya’s Steps implemented in the experimental class proved to be more effective in fostering critical thinking skills compared to the discovery learning model used in the control class.